2003
DOI: 10.1523/jneurosci.23-21-07776.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transient Activation of Superior Prefrontal Cortex during Inhibition of Cognitive Set

Abstract: The prefrontal cortex implements a set-shifting function that includes inhibition of a previously acquired cognitive set. The impairment of the inhibitory function results in perseverative behavior that forms one characteristic feature of frontal lobe dysfunction. Previous neuroimaging studies have revealed inhibitory mechanisms in the inferior prefrontal cortex. The present functional magnetic resonance imaging study devised "dual-match" stimuli in a set-shifting paradigm that allowed us to temporally isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
51
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 52 publications
5
51
2
Order By: Relevance
“…In our results, more robust group differences are found in the NoGo than Go condition, showing dysfunction in response inhibition (NoGo) related oscillatory activity in OA subjects. Many fMRI and lesion studies implicate the prefrontal areas as the neural basis for response inhibition (e.g., Konishi et al 1999Konishi et al , 2003Liddle et al 2001;Watanabe et al 2002). We suggest that this frontal dysfunction may be due to the dysregulation in inhibitory rhythms (theta oscillations) and/or potentials (No-Go P3, P3a, N2, etc), and this dysfunction is common across a variety of disinhibitory spectrum disorders.…”
Section: Discussionmentioning
confidence: 82%
“…In our results, more robust group differences are found in the NoGo than Go condition, showing dysfunction in response inhibition (NoGo) related oscillatory activity in OA subjects. Many fMRI and lesion studies implicate the prefrontal areas as the neural basis for response inhibition (e.g., Konishi et al 1999Konishi et al , 2003Liddle et al 2001;Watanabe et al 2002). We suggest that this frontal dysfunction may be due to the dysregulation in inhibitory rhythms (theta oscillations) and/or potentials (No-Go P3, P3a, N2, etc), and this dysfunction is common across a variety of disinhibitory spectrum disorders.…”
Section: Discussionmentioning
confidence: 82%
“…The left inferior and middle frontal cortex has been implicated in response inhibition [Konishi et al, [2003]; Rubia et al, [2003]; Schulz et al, [2004]] and memory suppression ]; however, the functions of this area extend beyond response inhibition. Joint activation of the inferolateral frontal cortex (BA 44-47) and the SMA (BA 6) has been associated with generation of language and other speech (e.g., sign-language) [Horwitz et al, [2003]] and response selection in paradigms requiring task switching or outcome assessment [Lau et al, [2004]; Paulus et al, [2004]; Rowe et al, [2000]; Turk et al, [2004]; Zhang et al, [2004]].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous behavioral studies have demonstrated that the interference continues even after the first inhibition trial over the time scale of a minute or so, and therefore the previous set needs to be inhibited even after the first trial to avoid perseverative errors (9). Previous investigations of inhibitory mechanisms have focused on the first inhibition trial, whether the first trial was given immediately after the change (11)(12)(13)(14)(15)(16)(17)(18) or separated away from the change (19). Despite the abundant knowledge about the inhibitory mechanisms recruited at the first inhibition trial, little is known about the neural mechanisms responsible for the inhibition of the prolonged interference that persists long after the first inhibition trial.…”
mentioning
confidence: 99%
“…Despite the abundant knowledge about the inhibitory mechanisms recruited at the first inhibition trial, little is known about the neural mechanisms responsible for the inhibition of the prolonged interference that persists long after the first inhibition trial. To explore the neural substrates for the inhibition of the prolonged interference, the present functional magnetic resonance imaging (fMRI) study used a ''dual-match stimulus'' in a modified version of the WCST (19) that exempted subjects from inhibiting a previously acquired set (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation